How Do Maternal Subclinical Symptoms Influence Infant Motor Development during the First Year of Life? - Piallini, Giulia; Brunoro, Stefania; Fenocchio, Chiara; Marini, Costanza; Simonelli, Alessandra; Biancotto, Marina; Zoia, Stefania (Frontiers in Psychology, 2016)
An unavoidable reciprocal influence characterizes mother-infant’s dyad.Within this relationship,the presence of depression,somatization,hostility,paranoid ideation and interpersonal sensitivity symptoms at a subclinical level and their possible input on infant motor competences has not been yet considered.Bearing in mind that motor abilities represent not only an indicator of infant’s health-status,but also the principal field to infer his/her needs, eelings and intentions,in this study the quality of infants’movements were assessed and analyzed in relationship with the maternal attitudes.The aim of this research was to investigate if/how maternal symptomatology may lead infant's motor development during his/her first year of life by observing the characteristics of motor development in infants aged 0-11months.Participants included 123 mothers and their infants (0-11months-old).Mothers’ symptomatology was screened with SymptomChecklist-90-Revised(SCL-90-R),while infants were tested with Peabody Developmental Motor Scale-Second Edition.All dyads belonged to a non-clinical population, however,on the basis of SCL-90-Rscores, mothers’sample was divided into two groups: normative and subclinical.Descriptive,T-test,correlational analysis between PDMS-2scores and SCL-90-R results are reported,as well as regression models results.Both positive and negative correlations were found between maternal perceived symptomatology,Somatization(SOM),Interpersonal Sensitivity(IS),Depression(DEP),Hostility(HOS)and Paranoid Ideation(PAR)and infants’motor abilities.These results were then further verified by applying regression models to predict the infant motor outcomes on the basis of babies’ age and maternal status.The presence of positive symptoms in SCL-90-Rquestionnaire (subclinical group) predicted good visual-motor integration and stationary competences in the babies.In particular,depressive and hostility feelings in mothers seemed to induce an infant motor behavior characterized by a major control of the environmental space.When mothers perceived a higher level of hostility and somatization their babies showed difficulties in sharing action space, like required in the development of stationary positions and grasping objects abilities.In a completely different way,when infants can rely on a mother with low-perceived symptoms(normative group)his/her motor performances develop with more degree of freedom/independence.These findings suggest,for the first time,that even in a non-clinical sample,mother's perceived-symptoms can produce important consequences not in infant motor development as a whole,but in some specific areas,contributing in shaping the infant motor ability and his/her capability to act in the world.